Blood Pressure Profile and Hypertension in Urban Adolescents: Need for Cognisance - Faujdar, Dharmajeet Singh; Kunte, Renuka; Bhalwar, Rajvir (Journal of Nepal Paediatric Society, 2014)
Objective: To find the profile of blood pressure and the prevalence of hypertension in adolescents in an urban area. Methods: A cross sectional study was carried out in Adolescent students in the age group of 11-17 years, in a school in an urban area of Pune, belonging to upper socioeconomic group to measure their blood pressure and anthropometric parameters. Results: The mean SBP and DBP in both boys and girls were found to increase with increasing age and anthropometric measurements. The prevalence of hypertension was 12.23% in boys and 10.1% in girls and the prevalence of overweight as per BMI was 19.14% in boys and 18.62% in girls. The prevalence of hypertension observed in overweight children (36.1% in boys 30.8% in girls) was significantly (p<0.000) higher than normal weight children (6.5% in boys and 5.36% in girls). Among the anthropometric variables only weight & BMI had moderately strong correlation with SBP(r-0.559 &0.506). Conclusion: Hypertension is prevalent among adolescent population and overweight/obesity has been found to play a crucial role in predicting rise in BP in them. It is recommended bp monitoring be made mandatory part of school health services programme for early detection & instituting preventive measures. DOI: http://dx.doi.org/10.3126/jnps.v34i2.10743 J Nepal Paediatr Soc 2014;34(2):85-89